Serum Uric Acid and Progression of Autosomal Dominant Polycystic Kidney Disease: Results from the HALT PKD Trials - Brosnahan, Godela M.; You, Zhiying; Wang, Wei; Gitomer, Berenice Y.; Chonchol, Michel (Current Hypertension Reviews, 2021)
Background: Epidemiological studies have suggested that elevated serum uric acid may contribute to the progression of chronic kidney disease. However, no large prospective study has examined whether hyperuricemia is an independent risk factor for the progression of autosomal dominant polycystic kidney disease (ADPKD). Methods: We measured uric acid in stored serum samples from the 2-year study visit of 671 participants from the HALT PKD multicenter trials. Participants were categorized according to uric acid tertiles. For Study A (participants aged 15-49 years with preserved kidney function, n=350), we used linear mixed effects models to examine the association between uric acid and repeated measures of height-adjusted total kidney volume (htTKV), the primary outcome for Study A. For Study B (participants aged 18-64 with decreased kidney function, n=321), we used Cox proportional hazards models to assess the hazard for the combined endpoint of 50% loss in estimated glomerular filtration rate (eGFR), end-stage kidney disease (ESKD), or death, the primary outcome for Study B. To assess the association of uric acid with the slope of eGFR decline (secondary outcome of HALT A and B), we used linear mixed effects models for the combined population of Study A and B. Results: In the unadjusted model, the annual change in htTKV was 2.7% higher in the highest uric acid tertile compared to the lowest (p<0.001), but this difference became insignificant after adjustment for gender. Men had faster TKV growth than women (p<0.001). There was no difference in eGFR decline between the 3 uric acid tertiles. Hazard ratios for the clinical endpoint were 2.9 (95% confidence interval, 1.9-4.4) and 1.8 (1.1-2.8) respectively in the high and medium uric acid groups in unadjusted and partially adjusted models (p<0.001), but the significance was lost after adjustment for baseline eGFR. Results were similar when uric acid was examined as a continuous variable. Conclusion: Elevated serum uric acid is not an independent risk factor for disease progression in ADPKD.
Keywords: Autosomal dominant polycystic kidney disease